O Periquitinho Sarnento (2024): uma tradução transcultural da obra de José Joaquín Fernández de Lizardi (1816) para o português brasileiro – reflexões sobre o primeiro romance latino-americano - González, Leila Shaí Del Pozo (2024)
The corpus of this study focuses on El Periquillo Sarniento (1816), by the Mexican José Joaquín Fernández de Lizardi (1776-1827), a work without known translation into Portuguese to this day. This translation is a perspective considered in the research proposals of the Group “Remeanings of the past in America: reading, writing and translation of the hybrid genres of history and fiction – ways to decolonization”, and it fits itself in the expectations of the Post-Graduation Program in Language and Literature – PPGL – of UNIOESTE/Cascavel-PR. Our reading conducted us to clearly understand that the importance of this work by Fernández de Lizardi does not fall only in the fact that it is the first novel written in Latin America, but, also, by being from 1816 and to embody in its diegesis (Genette, 1979) the criticality embedded in the Latin American literary expressions from the mid-20th century that Santiago enunciated in the 1970s. This way, it is fundamental that we translate it to the Brazilian Portuguese language with the objective of retrieving and remeaning this first Latin American novel by the paths of decolonization. The objective of this thesis is to translate El Periquillo Sarniento (1816), by Fernández de Lizardi, to Brazilian Portuguese and to present a reflexive study about the work. Our research is bibliographic and the criteria are of qualitative research. Thus, in this study, we rely on the contributions of Choza and Ponce-Ortiz (2010), Ruiz Barrionuevo (2008), Palazón Mayoral (2001, 2012, 2016), Silva and Dantas (2017). Next, by bringing some theoretical foundations about the picaresque of the 15th and 16th century, we reflect on the anthropophagic and transcultural process (Rama, 2008) that Fernández de Lizardi carries out on them, supported by the assumptions of González (1988; 1994; 2010), Ferreira (2008), Ruiz Barrionuevo (2008), Bobadilla Encinas (2008), Rosetti (2011), Palazón Mayoral (2013) and Botoso (2016), among others. The comparative literature studies are done based upon Uslar Pietri (1969), Pérez Firmat (1990), Paz (1981; 1991; 1994; 1998), Bellei (2000), Coutinho (1995; 2003; 2004). By approaching the novel as a narrative from the 19th century, its impact at the time and the relations of this impact in Brazil, we make use of, in specific, the studies of Candido (1975), Lajolo and Zilberman (1998), Ferreira (2000), Silva (2004; 2009), Ferreira Jr. (2010), Almeida (2011), Cerqueira (2011; 2013), Oliveira and Oliveira (2014). Finally, we approach the contemporary theories that refer to the translation process, highlighting the studies of Even-Zohar (1990), Lefevere (1994), Villalta (1997), Rodrigues (1999), Pagano (2000), Bassnett (2003), Wyler (2003), Venuti (2002), Martins (2011), among others. This research contributes to filling the existing gap in the knowledge of the trajectory of Latin American/Hispanic American literature in the Brazilian reader, as well as in the readers of all other Portuguese-speaking peoples and ways for the still necessary awareness, in Latin American, of the rooted colonizing actions operated from the spaces of power (Bourdieu, 1989).